2010
DOI: 10.1099/ijs.0.013664-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter arachidis sp. nov., a plant-growth-promoting diazotrophic bacterium isolated from rhizosphere soil of groundnut

Abstract: A methylotrophic nitrogen-fixing bacterial strain, Ah-143 T , isolated from the rhizosphere soil of field-grown groundnut was analysed by a polyphasic taxonomic approach. Comparative 16S rRNA gene sequence analysis combined with rpoB gene sequence analysis allocated strain Ah-143 T to the family Enterobacteriaceae, with Enterobacter radicincitans and Enterobacter cowanii as the closest relatives. The strain is Gram-stain-negative, non-spore-forming, aerobic and motile, having straight rod-shaped cells with a D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 40 publications
4
35
1
Order By: Relevance
“…The component C 17 : 0 was found in three members of the genus Yersinia tested in this study and has been reported for the genus Yersinia and other genera within the family Enterobacteriaceae by other authors (Jantzen & Lassen, 1980;Kämpfer et al, 2005;Whittaker et al, 2005;Madhaiyan et al, 2010;Rameshkumar et al, 2010).…”
supporting
confidence: 89%
“…The component C 17 : 0 was found in three members of the genus Yersinia tested in this study and has been reported for the genus Yersinia and other genera within the family Enterobacteriaceae by other authors (Jantzen & Lassen, 1980;Kämpfer et al, 2005;Whittaker et al, 2005;Madhaiyan et al, 2010;Rameshkumar et al, 2010).…”
supporting
confidence: 89%
“…Although K. sacchari was not included in the study of Hardoim et al (2013), low similarities (90.8 % and 92.0 %; Table S4) between strains LMG 26429 T and LMG 26432 T and K. sacchari LMG 26783 T showed that strains LMG 26429 T and LMG 26432 T represent two different species from K. sacchari. Hardoim et al (2013) reported that the DNA-DNA relatedness values between K. radicincitans LMG 23767 T and K. oryzae LMG 24251 T , between K. radicincitans LMG 23767 T and K. arachidis KCTC 22375 T , and between K. oryzae LMG 24251 T and K. arachidis KCTC 22375 T were 79±6 % (higher than the result reported by Peng et al in 2009), 66±17 % (higher than the result reported by Madhaiyan et al in 2010) and 71±2 %, respectively, suggesting these three species probably had a close relationship. In the present study, four housekeeping gene sequences (rpoB, atpD, gyrB and infB) were available for all these three species, so their taxonomic status was re-examined by multilocus sequence analysis based upon concatenated partial rpoB, atpD, gyrB and infB gene sequences.…”
mentioning
confidence: 54%
“…Distinction of K. arachidis and K. radicincitans was also supported by fatty acid profiles (Madhaiyan et al, 2010;Hardoim et al, 2013).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“… Enterobacter cowanii [1], E. radicincitans [2], E. oryzae [3], E. arachidis [4], E. sacchari [5], E. oryziphilus [6, 7], and E. oryzendophyticus [6, 7] have been transferred into the novel genus Kosakonia of the family “ Enterobacteriaceae ” [8–10]. A novel species “ Kosakonia pseudosacchari” [11] closely related to K. sacchari was recently proposed.…”
Section: Introductionmentioning
confidence: 99%